The assessment of occupational disease among the employees of the metallurgical industry in the Zaporizhzhia region - Шаравара, Лариса Павлівна; Sharavara, L. P. (Dresden: Deutschland, 2019)
Occupational morbidity in Ukraine is a complex socio-economic, medical and hygienic problem. It is a component of the general morbidity of the population, which covers the category of diseases that arise as a result of the adverse factors of the productive environment and labor process.
Keywords: тези